Indigenous environmental justice - Jarratt-Snider, Karen; Nielsen, Marianne O. (Indigenous justice, 2020)
Powerful parallels: deep ecology and the writings of Vine Deloria Jr. -- Environmental injustice, land, and American Indian religious freedom -- Environmental injustices and state-corporate crime on Navajo and Hopi lands -- Environmental racism: contaminated water in indigenous and minority communities -- Two cases of navigating legal complexity: environmental justice in Barrow and Tar Creek -- The water-energy nexus and environmental justice: the missing link between water rights and energy production on tribal lands -- Not in our lands: a Canadian comparative case study of indigenous resistance strategies to natural resource development in British Columbia and the Arctic -- Urban Native American women as environmental justice leaders.